Solar-powered parallel irrigation with IoT monitoring system - Muhammad Arif, Osman; Roshahliza, M. Ramli; Nadzirah, Mohd Mokhtar; Putri Nur Farhanah, Mohd Shamsuddin; Jabbar, Waheb A. (School of Engineering, Taylor’s University, 2023)
Climate change affects the rainy and dry seasons, making it challenging to store and effectively utilize water resources. This problem will lead to crop losses and poor productivity in agriculture. A smart irrigation system in agriculture could be a solution by giving the ability to monitor the irrigation of the crops. An automated irrigation system might irrigate the crops and efficiently use the available water supplies. This study proposes an irrigation system using parallel water dripping system that is controlled and monitored using a Wi-Fi network, a wireless transceiver module, and a Real Time Clock (RTC) module. With the aid of this system, it is easier to control the solenoid water valve by using either manually on or off switch operations or a timer-based operation. The proposed irrigation system is also capable to be set for 5, 7, and 10 minutes from the developed system interface. Besides that, a multiple wireless sensor network were also integrated to observe the condition of the soil moisture and display it on the developed interface. The result showed that the sensor network detected the soil moisture content during the assigned watering time with about 83% accuracy based on two watering time conditions on three sensors. The soil moisture condition could be used as a parameter to let the irrigation operate based on the soil moisture data obtained from the sensors.